Anaesthesia and the patient with diabetes. Issue 3 (July 2015) - Stevanovic, Ksenija; Sabljak, Vera; Toskovic, Anka; Kukic, Biljana; Stekovic, Jovana; Antonijevic, Vesna; Kalezic, Nevena
Abstract: Aims: To provide updated knowledge regarding the airway management and the possibility of difficult intubation in diabetic patients. Materials and methods: We preformed a systematic literature review of the English language literature, published over the past 10 years which deals with this subject. Results: The vast majority of the modern literature data supports the fact that diabetic population has higher risk for difficult intubation occurrence. The most important characteristics of diabetic patients that are considered to be contributing factors for the difficult intubation are obesity, increased neck circumference and stiff joint syndrome. Conclusion: A special attention and thorough preoperative preparation should be given to patients with diabetes. In order to predict and prevent difficult intubation in these patients, further studies are needed to investigate this issue closely.